1998
DOI: 10.1021/jp982835q
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Titanium Oxide Photocatalysts Anchored on Porous Silica Glass by a Metal Ion-Implantation Method and Their Photocatalytic Reactivities for the Degradation of 2-Propanol Diluted in Water

Abstract: Highly dispersed titanium oxide photocatalysts anchored onto transparent plates of porous silica glass were successfully prepared by metal ion implantation, and their photocatalytic reactivity for the liquid-phase photocatalytic degradation of an aqueous 2-propanol solution was compared with that in an aqueous TiO2 dispersion. The titanium ions implanted into the porous silica glass are found to be present on the surface layer as isolated tetrahedral titanium oxide moieties by diffuse reflectance absorption, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
137
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(141 citation statements)
references
References 20 publications
2
137
0
2
Order By: Relevance
“…The implantation of various transition-metal ions such as V 5+ , Cr 3+ , and Cu 2+ into the lattice of Ti 4+ in anatase thin films was investigated by Anpo et al [62][63][64][65][66][67]. The photoreactivities of chemically modified anatase thin films decreased under UV irradiation, although those anatase thin films modified with transition-metal ions can behave as photocatalysts under Vis irradiation.…”
Section: Vis-responsive Anatase Thin Film Fabricated Using the Mpmmentioning
confidence: 99%
“…The implantation of various transition-metal ions such as V 5+ , Cr 3+ , and Cu 2+ into the lattice of Ti 4+ in anatase thin films was investigated by Anpo et al [62][63][64][65][66][67]. The photoreactivities of chemically modified anatase thin films decreased under UV irradiation, although those anatase thin films modified with transition-metal ions can behave as photocatalysts under Vis irradiation.…”
Section: Vis-responsive Anatase Thin Film Fabricated Using the Mpmmentioning
confidence: 99%
“…Similar results have been observed by Anpo and coworkers. [10][11][12] The shift of the absorption edge to higher wavelengths with increasing monolayer coverage is due to the development of the band structure in the photocatalyst and is well known to occur in semiconductor nanoparticles. The single monolayer catalyst consists of an assembly of individual titanium-oxygen complexes.…”
Section: Tio2/pvg Multilayer Catalysts 1 Catalyst Characterizationmentioning
confidence: 99%
“…In contrast to our findings in the gas-phase, Anpo and coworkers observed that the single monolayer TiO2/PVG catalyst was the most photoreactive in the oxidation of the liquid-phase oxidation of 1-octanol in acetonitrile with O2 and in the liquid-phase oxidation of 2-propanol diluted in water with O2. 11,12 In situ SSNMR studies of the photocatalytic oxidation of acetone on the single monolayer TiO2/PVG catalyst and Degussa P-25 TiO2 powder show that the presence of a surface bound epoxide species (CH3CHCH2O, ∼50 ppm) is required for the effective photocatalytic oxidation of acetone. 23 The epoxide species was only found on the TiO2/PVG catalysts.…”
Section: Photocatalytic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, several strategies including the doping of TiO 2 with transition metal ions [15][16][17], the synthesis of reduced forms with TiO 2-x structure by the plasma treatment [18,19], anchoring organic dyes onto the surface of TiO 2 , and the doping of TiO 2 with anionic nonmetals have been investigated [20][21][22][23][24][25]. However, the photocatalytic activity of metal doping is impaired by thermal instability [26] and an increase in carrier-recombination facilities [27]. In dye sensitized TiO 2 , all of the known sensitizers are toxic and unstable in aqueous solution, thus making them unsuitable for application in photocatalysis [28].…”
Section: Introductionmentioning
confidence: 99%